Determinan Yang Mempengaruhi Kinerja Karyawan Pada Bank BRI Cabang Kramat Jati Jakarta - Hepi Prayudiawan (Faculty of Economic and Business, 2016)
The Determinant that Influence Employee Performance in Bank of BRI Branch of Kramat Jati JakartaThere are a lot of factors that determine the employee performance, included competence, working disciplines, and working environment. The aim of this study is to determine the impact of competence, working disciplines, and working environment on Employee Performances in Bank of BRI, Kramat Jati Branch. The analysis method that used in this research is multiple regression. The result shows that the competence and working environment have a positive impact on employee performance. But, the working discipline don’t has an impact on employee performance. There are several implication of this research, such as: first, the company should recruit the employee with good competency. Second, the company should create a conducive working environment. Third, the company should have a good regulation to make sure the working disciplineDOI: 10.15408/ess.v6i2.3556